1998
DOI: 10.1098/rspb.1998.0295
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Leavenworthia populations with different inbreeding levels

Abstract: Levels of neutral genetic diversity within and between populations were compared between outcrossing (self-incompatible) and inbreeding populations in the annual plant genus Leavenworthia. Two taxonomically independent comparisons are possible, since self-incompatibility has been lost twice in the group of species studied. Within inbred populations of L. uni£ora and L. crassa, no DNA sequence variants were seen among the alleles sampled, but high diversity was seen in alleles from populations of the outcrosser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 74 publications
5
82
3
Order By: Relevance
“…First, data on allozyme variation in both plants (Hamrick andGodt 1990, 1996) and animals (Jarne 1995) have shown that inbreeding species have lower neutral genetic diversity within populations than more outcrossing taxa. Recent studies, using molecular data have verified this observation and also shown that neutral genetic diversity at the species level is often lower in inbreeding species, compared to closely related, more outcrossing species, although this effect is far less pronounced than within-population diversity (Bergelson et al 1998;Dvořák et al 1998;Liu et al 1998Liu et al , 1999Stephan and Langley 1998;Charlesworth and Pannell 2001). The second observation of the effects of mating system is that levels of genetic differentiation among populations, measured as F ST or related statistics, are generally higher in inbreeding species than in outcrossing species (Hamrick andGodt 1990, 1996;Charlesworth and Pannell 2001).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…First, data on allozyme variation in both plants (Hamrick andGodt 1990, 1996) and animals (Jarne 1995) have shown that inbreeding species have lower neutral genetic diversity within populations than more outcrossing taxa. Recent studies, using molecular data have verified this observation and also shown that neutral genetic diversity at the species level is often lower in inbreeding species, compared to closely related, more outcrossing species, although this effect is far less pronounced than within-population diversity (Bergelson et al 1998;Dvořák et al 1998;Liu et al 1998Liu et al , 1999Stephan and Langley 1998;Charlesworth and Pannell 2001). The second observation of the effects of mating system is that levels of genetic differentiation among populations, measured as F ST or related statistics, are generally higher in inbreeding species than in outcrossing species (Hamrick andGodt 1990, 1996;Charlesworth and Pannell 2001).…”
mentioning
confidence: 89%
“…Recent work has extended these results to structured populations and shown that partial selfing can be incorporated into the standard population genetic theory for random mating populations if effective population size is reduced according to equation (1) (Maruyama and Tachida 1992;Tachida and Yoshimaru 1996). Several recent empirical studies, however, have found that reductions in genetic diversity within populations of inbreeding species are far greater than the expected reductions based on the reduced effective population size (Jarne 1995,Dvořák et al 1998Liu et al 1998Liu et al , 1999. At least three different processes are potentially able to cause these patterns.…”
Section: Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Although predominantly selfing species often have less genetic variation than cross-fertilizing species in nuclear genome (Baudry et al, 2001;Graustein et al, 2002;Hamrick and Godt, 1996;Liu et al, 1999Liu et al, , 1998Savolainen et al, 2000; but see Wright et al, 2002), substantial genetic variations do exist in highly selfing populations (Hedrick, 1998). The maintenance of nuclear polymorphisms has been the subject of a few studies and the exact conditions have been obtained Hedrick, 1998).…”
Section: Introductionmentioning
confidence: 99%